2017
DOI: 10.1007/s00268-017-4373-0
|View full text |Cite
|
Sign up to set email alerts
|

Early Seizure Prophylaxis in Traumatic Brain Injuries Revisited: A Prospective Observational Study

Abstract: The present study failed to show any benefit of routine early seizure prophylaxis following blunt TBI. This practice should be reexamined in a large randomized clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…The incidence of EPTS ranges from 0.4% to 26.7%, depending on study population and methods for seizure detection 9–12 . They are associated with increased intracranial pressure, worsening cerebral edema, and metabolic crisis 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of EPTS ranges from 0.4% to 26.7%, depending on study population and methods for seizure detection 9–12 . They are associated with increased intracranial pressure, worsening cerebral edema, and metabolic crisis 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Although several therapeutic targets have been ascribed for levetiracetam, it is clear that it modulates the synaptic vesicle glycoprotein 2A, with consequent reduction of the release of synaptic excitatory neurotransmitters, restoring the balance between inhibitory and excitatory synaptic activities [ 3 , 4 , 5 , 6 , 7 ]. This unique mechanism of action may be linked with the usefulness of levetiracetam for the management of status epilepticus in pediatric and adult patients [ 8 , 9 , 10 , 11 , 12 ], prophylaxis of seizures from post-traumatic brain injury [ 13 , 14 , 15 , 16 , 17 ], neuropathic pain [ 18 ], and some psychiatric pathologies [ 19 ]. Moreover, its safety profile and linear pharmacokinetics, together with its low ability to cross the placental barrier, make levetiracetam a first-line option in pregnant women with epilepsy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…An additional 53 articles were excluded as these did not meet the eligibility criteria of this meta-analysis. Finally, 25 articles with a total sample size of 6,466 cases were included in the network meta-analysis, including seven randomized controlled trials ( Young et al, 1983a ; Young et al, 1983b ; Temkin et al, 1990 ; Temkin et al, 1999 ; Szaflarski et al, 2010 ; Khan et al, 2016 ; Younus et al, 2018 ), four prospective studies ( Jones et al, 2008 ; Inaba et al, 2013 ; Gabriel and Rowe, 2014 ; Khor et al, 2018 ), 13 retrospective studies ( Wohns and Wyler, 1979 ; Servit and Musil, 1981 ; Ma et al, 2010 ; Debenham et al, 2011 ; Caballero et al, 2013 ; Kruer et al, 2013 ; Bhullar et al, 2014 ; Javed et al, 2016 ; Zangbar et al, 2016 ; Hazama et al, 2018 ; Kwon et al, 2019 ; Harris et al, 2020 ; Nguyen et al, 2021 ), and one non-randomized trial ( Klein et al, 2012 ) as shown in Figure 1 . The characteristics of the study design, interventions, and sample size for each treatment group are summarized in ( Tables 1 , 2 ).…”
Section: Resultsmentioning
confidence: 99%